Factors influencing health-related quality of life in children with asthma: insights from Addis Ababa public hospitals - Tsehaynew Kasse; Selemaye Zenebe; Yalemzer Agegnehu; Arega Abebe Lonsako (Frontiers in Public Health)
BackgroundBronchial asthma is a global health problem in particular a respiratory condition characterized by broncho spasms that negatively affect the quality of life (QOL) of children. However, there is a paucity of data regarding the health-related quality of life of asthma in children in Ethiopia, and the study area.ObjectiveThe objective of this study was to assess the health-related quality of life among asthmatic children aged 7–17 in selected hospitals in Addis Ababa, Ethiopia.MethodsAn institutional-based analytical cross-sectional study involving 136 asthmatic children aged 7–17 years was conducted in the selected hospital in Addis Ababa, from February to April 2024. Respondents were chosen using a systematic random sampling method. Structured, interviewer-administered, and pretested questionnaires, were used to collect data. The data were coded and entered into Epi-Data 3.1 before being exported to SPSS version 25 for analysis. Logistic regression was employed to identify factors influencing health-related quality of life Statistical significance was set at p < 0.05 with a 95% confidence interval.ResultsThe study found that 46% [95% CI: 37.6–54.4%] of the study participants had a poor quality of life. Factors associated with an increased likelihood of poor quality of life included caregivers’ lack of formal education (Adjusted Odds Ratio [AOR]: 1.39 [1.80–10.69]), a family history of asthma (AOR: 2.51 [1.46–4.299]), longer asthma duration (AOR: 3.47 [1.89–6.39]), uncontrolled asthma (AOR: 3.47 [1.89–6.39]), moderate persistent asthma (AOR: 2.4 [1.40–4.20]), and comorbidities (AOR: 2.4 [1.40–4.20]).ConclusionThe study highlights almost half of asthmatic children had a poor quality of life in Addis Ababa. Factors such as caregivers’ lack of formal education, a family history of asthma, longer duration and increased severity of asthma, uncontrolled asthma, and comorbidities were significantly associated with poor quality of life. Therefore, implementing targeted education programs, encouraging family history assessments, and strengthening comorbidity screening and management for children and their families in Addis Ababa are recommended.